Rural Micro-entrepreneurship and Asset Management Support by a Locally Embedded Civil Society Organization : An Exploratory Case Study in Pakistan - Raja, Sania Sarfraz; Arslan, Ahmad; Hussain, Syed Mujahid (Routledge, 2024)
This chapter is one of the pioneering academic endeavors to assess asset management support offered by locally embedded civil society organizations (CSOs) to rural micro-entrepreneurs in the emerging economy context of Pakistan. Most of the existing research on micro-entrepreneurship financing has so far mostly focused on startup financing and access to capital (primarily loans). However, a significant challenge for micro-entrepreneurs, particularly those operating in emerging economies’ rural contexts, is asset management in the pre-operational, operational, and post-operational phases of startup to ensure their businesses may survive and thrive. The current chapter analyzes the single in-depth case study of a local CSO (Khushal Dastkaar) active in rural settings (Chakwal in Punjab province of Pakistan) for micro-entrepreneurship development. Being locally embedded, the case CSO can undertake continuous monitoring and offer asset management support for home-based startups. We present the details of four micro-entrepreneurs as examples to specify the peculiarities of the support mechanisms and associated processes. The findings revealed the critical role of asset management support in ensuring the continued operation of these micro-entrepreneurs. Along with ensuring viable operations in the main line of business, innovative use of bought assets and diversification by sample micro-entrepreneurs was observed and the support offered by the locally embedded CSO was vital in this concern.
Keywords: Asset Management; Home-based startup; Micro; Rural; entrepreneurship; Pakistan